Zinc(II)-The Overlooked Éminence Grise of Chloroquine's Fight against COVID-19? - Aleksandra Hecel; Małgorzata Ostrowska; Kamila Stokowa-Sołtys; Joanna Wątły; Dorota Dudek; Adriana Miller; Sławomir Potocki; Agnieszka Matera-Witkiewicz; Alicia Dominguez-Martin; Henryk Kozłowski; Magdalena Rowińska-Żyrek (MDPI AG, 2020)
Zn(II) is an inhibitor of SARS-CoV-2's RNA-dependent RNA polymerase, and chloroquine and hydroxychloroquine are Zn(II) ionophores-this statement gives a curious mind a lot to think about. We show results of the first clinical trials on chloroquine (CQ) and hydroxychloroquine (HCQ) in the treatment of COVID-19, as well as earlier reports on the anticoronaviral properties of these two compounds and of Zn(II) itself. Other FDA-approved Zn(II) ionophores are given a decent amount of attention and are thought of as possible COVID-19 therapeutics.